2013
DOI: 10.1159/000351230
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion - the Art and Science of Compromise

Abstract: Many modern therapies depend on platelet (PLT) transfusion support. PLTs have a 4- to 7-day shelf life and are frequently in short supply. In order to optimize the inventory PLTs are often transfused to adults without regard for ABO compatibility. Hemolytic reactions are infrequent despite the presence of ‘high titer' anti-A and anti-B antibodies in some of the units. Despite the low risk for hemolysis, some centers provide only ABO identical PLTs to their recipients; this practice might have other beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 89 publications
(141 reference statements)
2
62
0
Order By: Relevance
“…These data suggest that the transfusion of incompatible plasma does not adversely affect a civilian trauma patient's clinical cours; however, LTOWB was not included in this study, hence its effect on clinical outcomes remains to be demonstrated in the civilian population. In addition, many of the PLT units that are transfused in the United States contain incompatible plasma, and the incidence of hemolysis is rare …”
mentioning
confidence: 99%
“…These data suggest that the transfusion of incompatible plasma does not adversely affect a civilian trauma patient's clinical cours; however, LTOWB was not included in this study, hence its effect on clinical outcomes remains to be demonstrated in the civilian population. In addition, many of the PLT units that are transfused in the United States contain incompatible plasma, and the incidence of hemolysis is rare …”
mentioning
confidence: 99%
“…Mitigation strategies used by different facilities include provision of ABO‐compatible plasma products, physician notification, volume reduction, washed platelets, antibody screening for high‐titer ABO antibodies, pooled platelets of assorted ABO donor types, and limited transfusions of out‐of‐group plasma products. The risk of a clinically significant acute hemolytic transfusion reaction associated with group O donor platelets transfused to non–group O recipients is relatively low, estimated to be about 1 in 9000 (0.01%) in one study and 0.05% in another study . These reactions are likely rare due to the neutralization of the anti‐A or anti‐B antibodies by the recipient's soluble or endothelial‐based A and B antigens and/or the dilution of the incompatible ABO antibodies in the recipient's plasma volume.…”
Section: Discussionmentioning
confidence: 98%
“…The observation that AB type TTP patients did not experience any clinical or laboratory exacerbation of hemolysis when a combination of AB and low titer A plasma was used is not surprising. Transfusion of ABO incompatible platelets is a common practice in medicine; hemolysis events from this ABO‐minor incompatibility is very rare and is further reduced when O group titered platelets are used . Group A plasma has been safely used in bleeding trauma patients and “Safety of the use of group A plasma in trauma: the STAT study” showed no difference in clinical outcomes between ABO identical group (A type patients that received A plasma) and ABO minor incompatible group (B/AB patients that received A plasma) .…”
Section: Discussionmentioning
confidence: 99%